Agents of sustainable change: the importance of leadership and responsibility in corporate sustainability - Keil, Maike; Michaux, Valerie; Ziefle, Martina; Arning, Katrin (Frontiers in Sustainability, 2025)
IntroductionAddressing climate change requires both individual behavioral change and corporate transformation, as organizations play a crucial role in a sustainable society. How sustainability in organizations is perceived and implemented, depends on diverse factors such as management practices, communication, individual attitudes, and behaviors of leaders and employees. However, current research only investigates factors that affect the implementation of sustainable development and practices separately. Hence, holistic approaches are required to provide insight into how they affect a company’s sustainability efforts.MethodsA quantitative online survey with n = 87 employees was conducted in Germany in 2023. The Corporate Sustainability Index (CSI) was developed to indicate the extent to which organizations implement sustainability into their policies and concrete practices. To investigate which factors predict corporate sustainability, we analyzed employee-, management-, and organization-related factors using multiple linear regression analysis.ResultsInstitutionalized responsibility for sustainability was the strongest predictor of the CSI, along with a top-down approach to implement corporate sustainability. In contrast, employees’ environmental awareness and their organizational citizenship behavior towards the environment were not related to CSI.Discussion and conclusionsOur results stress the importance of leaders with an environmental focus as role models who can drive the transformation towards effective sustainability management in companies. This study offers important insights into the prerequisites for leaders to foster an environmentally responsible culture in their organizations.